2018
DOI: 10.22270/jddt.v8i1.1546
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in Vitro Evaluation of Brands of Clotrimazole Cream Formulations Marketed in Ethiopia

Abstract: The aim of present work was to undertake comparative in vitro quality evaluation of six marketed clotrimazole cream formulations in Ethiopia with respect to physico-chemical properties like viscosity, spreadability, extrudability, pH and drug content. In vitro clotrimazole release from cream formulations was also studied using synthetic cellulose acetate membrane at 37 ºC in a solvent containing methanol and PBS 7.4 in the ratio of 75:25 as receiver medium. The cumulative amounts of the drug released over 12 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The spreadability of all the formulation was between 6.11±0.13 and 9.76±0.31 cm (Tables 4 and 5). Formulation JO 2 shows the highest spreadability; 9.76±0.31 cm and formulation CO 2 shows the highest [23]. Both the final formulations were subject further diffusion study with the marketed formulation and found that formulation CO 2 was the best formulation among two and shows a percent drug release of 61.98±1.10% (Table 8 and Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The spreadability of all the formulation was between 6.11±0.13 and 9.76±0.31 cm (Tables 4 and 5). Formulation JO 2 shows the highest spreadability; 9.76±0.31 cm and formulation CO 2 shows the highest [23]. Both the final formulations were subject further diffusion study with the marketed formulation and found that formulation CO 2 was the best formulation among two and shows a percent drug release of 61.98±1.10% (Table 8 and Fig.…”
Section: Discussionmentioning
confidence: 95%
“…After analyzing all the study of all formulations from different oils, the best-optimized formulation was evaluated based on in vitro diffusion studies. Optimized formulations were then compared with the marketed formulation [22,23].…”
Section: In Vitro Diffusion Studymentioning
confidence: 99%
“…The drug content was calculated according to beer lambert's law. 17,18 For the in-vitro diffusion study, the Franz Diffusion Cell was used; the base of the cell was covered with overnight wetted cellophane membrane. The 5gm of cream is transferred into the Franz Diffusion Cell.…”
Section: Drug Contentmentioning
confidence: 99%